Mini cutting technique: an easy and cost-effective way of Tinospora cordifolia multiplication - SARAN, PARMESHWAR LAL; PATEL, RIDDHIBEN; MEENA, RAM PRASNNA; KALARIYA, KULDEEPSINGH A.; CHOUDHARY, RAVISH (The Indian Journal of Agricultural Sciences, 2019)
The experiment was carried out to determine the commercially viable technique for multiplication of Tinospora cordifolia (Willd.) Miers ex Hook. F and Thoms (giloy). In the open field condition using the variable numbers of nodes per cutting were investigated and observed that three and four nodes cuttings were significantly superior in growth and survival parameters but involved more planting/stock materials. Therefore, to reduce the planting stocks, cuttings with one node with and without stem part were evaluated. Single bud cuttings with both side wood (stem part) showed significantly higher growth and survival percent in comparison to only bud without stem portion and bud with one side stem wood. Among all the tested technique, four buds’ technique was nearly found superior in growth parameters but not significant with three buds, which was proven for higher survival percent. However, single bud cutting technique involved minimum cost and economically proven superior for one-ha plantation as compare to available traditional techniques. The present study indicated that for T. cordifolia, mini cuttings (bud with both side stem wood) techniques is the best propagation method for commercial multiplication.